The Slowest Shared Resonance: A Review of Electromagnetic Field Oscillations Between Central and Peripheral Nervous Systems - Young, Asa; Hunt, Tam; Ericson, Marissa (Frontiers in Human Neuroscience, 2022)
Neural electromagnetic field oscillations are increasingly being viewed as causal drivers of consciousness. Recent research has highlighted the importance of the body’s various endogenous rhythms in organizing these neuronally generated fields through various types of entrainment. We expand this approach by examining evidence of extracerebral shared resonances between the brain and other parts of the body, in both humans and animals. We then examine the degree to which these data support one of General Resonance Theory’s principles: the Slowest Shared Resonance (SSR) principle, which states that the combination of micro- to macro-consciousness in coupled field systems is a function of the slowest common denominator frequency or resonance. This principle may be utilized to develop a spatial hierarchy of brain-body shared resonance systems. It is predicted that a system’s SSR decreases inversely with distance between resonating structures in the body. The various resonance relationships examined, including between the brain and gastric neurons, brain and sensory organs, and brain and spinal cord, generally match the predicted SSR relationships, empirically supporting this principle of General Resonance Theory.